DECISA Project (DErmatology Clinics in Italy: Survey on Alitretinoin): A real‐life retrospective cohort multicenter study on 438 subjects with chronic hand eczema. Issue 3 (9th March 2021) - Ferrucci, Silvia; Persichini, Paola; Gola, Massimo; Scandagli, Ilaria; Pigatto, Paolo; Legori, Agostina; Musumeci, Maria Letizia; Micali, Giuseppe; D'Agata, Elisabetta; Schena, Donatella; Azzolini, Alan; Gallo, Rosella; et al.
Abstract: Alitretinoin is the only systemic agent approved to treat moderate‐severe chronic hand eczema (CHE) unresponsive to potent topical corticosteroids. No nationwide Italian data regarding real‐life efficacy, safety, and tolerability of treatment are available. The DECISA project (DErmatology Clinics in Italy: Survey on Alitretinoin) retrospectively examined data from a registry including 15 Dermatology Clinics authorized to prescription of alitretinoin for CHE patients. Disease severity was assessed at baseline, and after 3 and 6 months of treatment, using the 5‐point Physician Global Assessment (PGA) and the modified Total Lesion‐Symptoms‐Severity (mTLSS) scores. Between November 2010 and July 2018, data of 248 male and 190 female patients (mean age 49.71 ± 13.20 years) treated with alitretinoin were collected. Of them, 43.2% had irritant contact dermatitis, 22.2% allergic contact dermatitis, 18.0% atopic dermatitis, 16.7% mixed (irritant/allergic) type of eczema. At 3 months, the 420 re‐evaluated patients showed significantly reduced mTLSS and PGA ( P < .0000001 vs baseline for both); PGA was clear/almost clear in 35.6% of cases. At 6 months, the 341 re‐evaluated patients showed significant ( P < .0000001) improvement of mTLSS and PGA vs baseline and 3 months (PGA clear/almost clear: 41.4%). Relapses occurred in 125 patients; 58 underwent an additional course of alitretinoin, with similarly good results. No relevant safety issues were reported; 86 patients experienced adverse effects, which forced 40 to prematurely stop treatment. The DECISA project results confirm the real‐life efficacy, safety and tolerability of alitretinoin in the treatment of moderate to severe CHE refractory to standard topical therapies.